The Role of the Circadian Clock in Hippocampal Aging and as a Therapeutic Target in Alzheimer's Disease - Adler, Paula (Université d'Ottawa / University of Ottawa, 2020)
Aging-associated cognitive impairment and neurodegenerative brain diseases such as Alzheimer's disease (AD) have profound global consequences, including significant health, social, and economic impacts. Rational therapeutic interventions that can effectively address sleep disturbances and memory impairment in people with AD, as well as the complex etiopathogenesis of the disease, remain major unmet clinical needs. The circadian clock represents a new potential therapeutic target for AD, given that its dysfunction may contribute to the development and clinical manifestations of the disease through regulation of sleep, hippocampal function, and neurodegeneration. Moreover, the identification of age-related changes in the circadian regulation of processes underlying memory function in the hippocampus may open new avenues to correct dysregulated rhythms and thereby prevent or reverse cognitive decline. In the first part of this thesis, young and middle-aged non-transgenic mice were compared using quantitative mass spectrometry in order to perform a proteome-wide screen for proteins with rhythmic abundances in the hippocampus and dissect changes in the temporal orchestration of biological pathways during aging. Aging disrupted circadian regulation of the hippocampal proteome and altered the daily expression profiles of proteins implicated in age-related neurodegenerative diseases and hallmarks of aging, suggesting that aging-induced changes in rhythmic physiology may play important roles in cognitive decline and aging-associated brain disorders such as AD. In the second part of this thesis, the therapeutic potential of a small molecule circadian clock modifier (PF-670462) was evaluated in 3xTg-AD mice using mass spectrometry–based proteomic analyses as well as cognitive and behavioural testing. PF-670462 reversed hippocampal proteomic alterations in several AD-related and clock-regulated pathways, rescued working memory deficits, and normalized behavioural circadian rhythm disturbances in 3xTg-AD mice. This study provides in vivo proof of concept for the efficacy of direct circadian clock modulation in a transgenic mouse model of AD. Together, these studies highlight emerging roles for the circadian clock in hippocampal aging and as a therapeutic target for AD.
Keywords: circadian; proteome; mass spectrometry; Alzheimer's disease; aging; hippocampus; casein kinase 1; 3xTg-AD